2018
DOI: 10.1159/000494238
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Enhances the Epithelial– Mesenchymal Transition of A549 Cells via miR3591-5p/USP33/PPM1A

Abstract: Background/Aims: Radiotherapy plays a critical role in lung cancer treatment. Radiation can activate transforming growth factor-β (TGF-β) signaling and induce the epithelial-mesenchymal transition (EMT), which may lead to distant metastases. MicroRNAs (miRNAs) have been suggested to affect radiotherapy in lung cancer. Methods: miRNA Next-Generation Sequencing was performed to investigate the effects of irradiation on the miRNA profile of lung cancer A549 cells. The functions of identified miRNA on the radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Significantly higher expression in stage III colon cancers from patients with recurrence and associated with poorer DFS 229 .miR-34b-5p−2.20Downregulated in breast tumors 166,230 .Tumor suppressormiR-34c-5p−2.36Downregulated in breast tumors 231 Tumor suppressormiR-3591-5p−2.88No reports for BCa. Expression increased after radiation of A549 NSCLC cells and Ubiquitin Specific Peptidase 33 (USP33) was a downstream target of miR-3591-5p 232 .miR-3663-5p−2.96No reports for BCa. Expression increased in human nonalcoholic fatty liver disease (NAFLD) 233 .miR-3912-3p−0.72No reports for breast or other cancers.miR-424-5p−1.18Increased in serum of BCa patients with resistance to dovitinib 234 .…”
Section: Resultsmentioning
confidence: 99%
“…Significantly higher expression in stage III colon cancers from patients with recurrence and associated with poorer DFS 229 .miR-34b-5p−2.20Downregulated in breast tumors 166,230 .Tumor suppressormiR-34c-5p−2.36Downregulated in breast tumors 231 Tumor suppressormiR-3591-5p−2.88No reports for BCa. Expression increased after radiation of A549 NSCLC cells and Ubiquitin Specific Peptidase 33 (USP33) was a downstream target of miR-3591-5p 232 .miR-3663-5p−2.96No reports for BCa. Expression increased in human nonalcoholic fatty liver disease (NAFLD) 233 .miR-3912-3p−0.72No reports for breast or other cancers.miR-424-5p−1.18Increased in serum of BCa patients with resistance to dovitinib 234 .…”
Section: Resultsmentioning
confidence: 99%
“…These data, produced by Ghosh et al, clearly indicate that the expression profile of microRNAs is a significant indicator of a therapy-resistant gene expression pattern [100]. This list can be extended with miR-3591-5p, which is the most significantly increased miRNA in response to radiation [102].…”
Section: The Path From Emt To Radio/chemoresistancementioning
confidence: 91%
“…Several pieces of evidence revealed that, if EMT is experimentally induced in cultured epithelial carcinoma cells, they will display cisplatin-resistance and radio-resistance [25]. Moreover, if, in a pure epithelial cancer cell culture, radio-resistance is induced [101,102], the resulting gene expression profile will resemble an EMT phenotype. A novel hypothesis suggests that EMT cells release membranous vesicles with a diameter of 40 to 100 nm, called exosomes, which are seen as functional mediators of a tumor-stroma interaction and of EMT.…”
Section: The Path From Emt To Radio/chemoresistancementioning
confidence: 99%
See 1 more Smart Citation
“…Increasing studies are pointing toward the involvement of PPM1A in the regulation of cell proliferation, migration, invasion, and differentiation . It is evident from several investigations that PPM1A emerges as a cancer suppressor in human malignancy . For instance, PPM1A is a RelA phosphatase with tumor suppressor‐like activity .…”
Section: Discussionmentioning
confidence: 99%